Risk factors for neonatal early-onset group B streptococcus-related diseases after the implementation of a universal screening program in Taiwan - Li-Chen Hung; Pei-Tseng Kung; Tsan-Hung Chiu; Hsun-Pi Su; Ming Ho; Hui-Fen Kao; Li-Ting Chiu; Kuang-Hua Huang; Wen-Chen Tsai (BMC, 2018)
Abstract Background We examined the risk for Group B streptococcus (GBS)-related diseases in newborns born to mothers who participated in a universal GBS screening program and to determine whether differences are observed in factors affecting the morbidity for neonatal early-onset GBS-related diseases. Methods This is a retrospective study and the study subjects were women who had undergone GBS screening and who gave birth naturally and their newborns between April 15, 2012 and December 31, 2013. Data from the GBS screening system database and the National Health Insurance database were collected to calculate the GBS prevalence in pregnant women and morbidity of newborns with early-onset GBS-related diseases. Results The GBS prevalence in pregnant women who gave birth naturally was 19.58%. The rate of early-onset infection caused by GBS in newborns decreased from the original 0.1% to 0.02%, a decrease of as high as 80%. After the implementation of the universal GBS screening program, only three factors, including positive GBS screening result (OR = 2.84), CCI (OR = 2.45), and preterm birth (OR = 4.81) affected the morbidity for neonatal early-onset GBS-related diseases, whereas other factors had no significant impact. Conclusion The implementation of the universal GBS screening program decreased the infection rate of neonatal early-onset GBS diseases. The effects of socioeconomic factors and high-risk pregnancy on early-onset GBS infections were weakened.